Adjunct fixation with a Kirschner wire or a plate for lateral unicondylar humeral fracture stabilization. Issue 7 (22nd June 2017) - Coggeshall, Jason D.; Lewis, Daniel D.; Iorgulescu, Alex; Kim, Stanley E.; Palm, Lindsey S.; Pozzi, Antonio
Abstract: Objective: To compare the biomechanical properties of using an interfragmentary 1.6 mm Kirschner wire or a 2.7 mm reconstruction plate as adjunctive epicondylar stabilization in simulated comminuted lateral unicondylar humeral fractures stabilized with a transcondylar 4.5 mm cortical screw. Study design: Cadaveric biomechanical assessment. Sample Population: Paired humeri harvested from 9 young, skeletally mature dogs. Methods: Simulated comminuted lateral unicondylar humeral fractures were stabilized with a transcondylar 4.5 mm cortical screw placed in lag fashion. Adjunct fixations consisting of a 1.6 mm Kirschner wire on one side, and a 2.7 mm reconstruction plate on the contralateral side, were tested within paired humeri. Repaired humeri were axially loaded to failure and construct stiffness, yield load, and load to failure were obtained from the load‐deformation curves. Results: Stiffness (mean ± SD: 577 ± 245 vs 310 ± 71 N/mm; P = .01), yield load (mean ± SD: 2389 ± 572 vs 1017 N ± 292; P = .0002), and load at failure (mean ± SD: 3351 ± 358 vs 1693 ± 363 N; P = .009) were greater in constructs incorporating a reconstruction plate rather than a Kirschner wire. Conclusion: Our results support the recommendation for adjunct fixation of comminuted lateral unicondylar humeral fractures with an epicondylar plate.